2017
DOI: 10.1111/ijd.13839
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based incidence and melanoma‐specific survival of cutaneous malignant melanoma in a Colombian population 2000–2009

Abstract: Conflicts of interest: None of the authors have any conflicts of interest to be reported, although Esther de Vries has received speaker honoraria to present population-based incidence rates of melanoma in several occasions. AbstractBackground Demographic, clinical, and morphological characteristics of cutaneous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 19 publications
3
36
1
6
Order By: Relevance
“…Nevertheless, it's important to mention that in 24% of cases, the specific site of the tumour was not provided. Series from some Latin-American countries have shown nodular melanomas as the predominant subtype, followed by superficial spreading, acrolentiginous and lentigo melanomas [28,29]; or, followed by lentigo [23] or acrolentiginuous melanomas [30]. In this study, as for high CM incidence areas worldwide, the most frequent histology in the country, and for the Centro and Patagonia regions, was the SSM.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, it's important to mention that in 24% of cases, the specific site of the tumour was not provided. Series from some Latin-American countries have shown nodular melanomas as the predominant subtype, followed by superficial spreading, acrolentiginous and lentigo melanomas [28,29]; or, followed by lentigo [23] or acrolentiginuous melanomas [30]. In this study, as for high CM incidence areas worldwide, the most frequent histology in the country, and for the Centro and Patagonia regions, was the SSM.…”
Section: Discussionmentioning
confidence: 62%
“…The primary location of melanomas differs between countries and populations. When analysing all RAMC cases together, regardless of gender, 28.6% of the lesions appeared in the trunk, as has been described in Spain [21] and Canada [22], but, for other Latin-American countries, the main location described was the lower limbs [23] or the face [24].…”
Section: Discussionmentioning
confidence: 65%
“…Its high degree of malignancy and high tendency to metastasize result in an unfavorable prognosis, since the overall five-year survival rate for patients with more than three metastases to lymph nodes or distant organs is less than 16 %, representing 90 % of deaths associated with skin tumors [5][6][7] . Interestingly, in Colombian studies, the overall melanoma-specific five-year survival rate is substantially lower than that reported by countries with higher incidence 8 .…”
Section: Introductionmentioning
confidence: 68%
“…Recently, molecular characterizations of ALM and mucosal melanoma (MCM) have shown that these clinical types are biologically distinct from the more common cutaneous melanomas. 6,7 Some reports indicated that these two subtypes correlated with poor survival, [8][9][10][11] while others have reported no correlation between clinical subtypes and prognosis. 12,13 The recent development of immune checkpoint inhibitors has dramatically changed the treatment of melanoma.…”
Section: Introductionmentioning
confidence: 99%